A new multiple integral inequality and its application to stability analysis of time-delay systems. (July 2020) - Tian, Yufeng; Wang, Zhanshan
Abstract: This paper focuses on the stability problem of linear time-delay systems. Firstly, a generalized vectors-based multiple integral inequality (GVMII) is presented, which can treat some existing results as its special cases. Secondly, based on the multiple integral inequality, a new delay-dependent stability criterion is derived for time-delay systems. Finally, a numerical example is given to illustrate the effectiveness of the stability criterion.